TRANSLATION TECHNIQUES OF RACIAL SLURS IN THE MOVIE '42' SUBTITLES - Nugroho, Muhammad Aprianto Budie; Agustiana, Vina; Budi, Farid Faqih Kusuma (UIN Raden Mas Said Surakarta, 2024)
This research aimed to classify racism slurs translation techniques in the subtitles of the movie entitled 42 made by professional (Netflix) and fan subtitlers (Movieku). It applied a qualitative approach with a case study design. For analyzing the data, it used document analysis with the objects the movie transcripts and subtitles. The data were analyzed by using the theory of translation technique from Molina and Albir (2002). From the total 192 data (96 for each category) there were found 11 types of translation techniques applied, i.e.: amplification, compensation, description, established equivalent, literal translation, linguistic compression, modulation, naturalization borrowing, particularization, pure borrowing, and reduction. The data show that both professional and fansub use more than one type of translation techniques that can be grouped into single (22.4%), duplet (58.8%), triplet (18.2%), and quartet group (0.5%). The frequency of occurrences of each group of the translation techniques in the professional subtitles are 20 times or 20.83% for single, 50 (52.08%) for duplet, 25 (26.04%) for triplet, and only 1 (1.04%) for quartet. In fansubs, there are 23 occurrences or 23.96% for single, 63 (65.62%) for duplet, 10 (10.41%) for triplet, and none for quartet. The result of this research is expected to be a reference for the other research with the same topic.